Emerging strategies for engineering Escherichia coli Nissle 1917-based therapeutics. (September 2022) - Lynch, Jason P.; Goers, Lisa; Lesser, Cammie F.
Abstract : Engineered microbes are rapidly being developed for the delivery of therapeutic modalities to sites of disease. Escherichia coli Nissle 1917 (EcN), a genetically tractable probiotic with a well-established human safety record, is emerging as a favored chassis. Here, we summarize the latest progress in rationally engineered variants of EcN for the treatment of infectious diseases, metabolic disorders, and inflammatory bowel diseases (IBDs) when administered orally, as well as cancers when injected directly into tumors or the systemic circulation. We also discuss emerging studies that raise potential safety concerns regarding these EcN-based strains as therapeutics due to their secretion of a genotoxic colibactin that can promote the formation of DNA double-stranded breaks in mammalian DNA. Highlights: Due to its genetic tractability; track record of safety in humans; and ability to home to, survive, and replicate in the gastrointestinal tract and tumors, Escherichia coli Nissle 1917 (EcN) has become a favored chassis for engineering 'smart microbes' that deliver therapeutic modalities to sites of disease. EcN variants engineered with new therapeutic properties via alterations in its metabolic pathways or the introduction of in situ drug delivery systems are showing promise for the treatment of bacterial infections, inflammatory bowel diseases, metabolic disorders, and cancer. Clinical trials are underway to test the safety and efficacy of EcN-based smart microbes for inborn diseases of metabolism and cancer. EcN synthesizes a genotoxin called colibactin capable of causing DNA double-strand breaks in mammalian cells, raising safety concerns about its use clinically.